Hybrid World War and the United States–China rivalry - Merino, Gabriel E. (Frontiers in Political Science, 2023)
The proposal of the article is to advance on the concept of Hybrid World War and to relate it to the conflict between the United States and China in the present historical-spatial transition of the world system. The concept of Hybrid World War is developed in contrast to that of the New Cold War, and in relation to the characteristics acquired by the world capitalist system from 1970 to 1980 as a transnational system of production, trade, and finance, the dynamics of strategic competition in the crisis of the unipolar globalist order, and the characteristics of the rise of China and its significance, different from that of the USSR. From this conceptual framework, the United States-China rivalry is observed, analyzing: the systemic tension between unipolarism and multipolarism, the central dispute in Asia Pacific, and the development of a war on all fronts or unrestricted.